Hubungan Burnout dengan Kualitas Hidup Perawat yang Merawat Pasien Pasca Strokedi Kota Samarinda : Literature Review - Winna Noor Cholifah; Suwaldi Pradana; Reylah Sepiah; Milkhatun Milkhatun (Lembaga Pengembangan Kinerja Dosen, 2026)
The phenomenon of burnout syndrome among nurses has become a critical issue that requires serious attention, considering nurses' role as frontline healthcare providers. Job burnout is influenced not only by physical workload but also by psychological factors, work environment conditions, social support, and individual resilience. This study aims to examine the relationship between burnout syndrome and nurses’ quality of life, as well as its impact on clinical service quality, particularly in post-stroke patient care. The research employed a literature review method by analyzing studies obtained from Google Scholar published between 2022 and 2025. A total of 20 articles that met the inclusion criteria were systematically reviewed. The findings indicate that burnout syndrome is characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment. A significant negative relationship was identified between the Quality of Nursing Work Life (QNWL) and burnout levels, indicating that poorer work-life quality increases the likelihood of burnout among nurses. Burnout was also found to negatively affect healthcare service standards, reduce empathy toward patients, and lower compliance with infection prevention and control protocols. Furthermore, the high prevalence of burnout contributes to increased turnover intentions among nurses. Psychological interventions, such as Mindfulness-Based Stress Reduction (MBSR) and psychoeducation, have been shown to effectively reduce burnout levels and improve emotional regulation. These findings highlight the importance of organizational strategies that support nurses’ well-being in order to enhance healthcare quality and patient safety.